Prevalence of iron deficiency in type 2 diabetes mellitus patients and its association with altered lipid profile - Arindam Naskar; Agnibho Mondal; Indranil Dhar (MGM Journal of Medical Sciences)
Background: The escalation of diabetes mellitus poses a significant public health challenge in India. This condition impacts iron metabolism, potentially causing variations in the iron profile. This study aimed to ascertain the prevalence of iron deficiency in individuals with type 2 diabetes mellitus and explore its associated factors. Materials and Methods: A cross-sectional study was conducted on adult patients with type 2 diabetes mellitus at a tertiary care center in Eastern India. Biochemical assessments encompassed fasting plasma glucose, post-prandial glucose, glycosylated hemoglobin (HbA1c), lipid profile, renal function tests, complete hemogram, and iron profile. Anthropometric measurements were conducted using standardized procedures. Results: This study revealed that among the 203 participants, the prevalence of iron deficiency was 63.5% (95% confidence interval: 56.5–70.2). Anemia was observed in 34% of patients (men <13 g/dL, women <12 g/dL). The mean levels of serum iron, ferritin, total iron binding capacity, and transferrin saturation were 62.9 ± 26.1 μg/dL, 100.6 ± 103.2 ng/mL, 392.3 ± 72 μg/dL, and 16.6 ± 7.5%, respectively. The mean fasting blood sugar, post-prandial blood sugar, and HbA1c values were 154.2 ± 63 mg/dL, 229.3 ± 92.1 mg/dL, and 7.7 ± 1.5%, respectively. There were no significant differences in iron levels between genders or between poorly controlled and well-controlled diabetics. However, significant associations were observed between iron deficiency and lower total cholesterol levels, low-density lipoprotein, and triglycerides. Conclusion: This study concludes that iron deficiency is highly prevalent among diabetic patients in India and is associated with lipid profile alterations.